Filogenia e variabilidade genética de Minaria (Apocynaceae): implicações para biogeografia e conservação da Cadeia do Espinhaço - Ribeiro, Patrícia Luz (2011)
The detection of areas that house a large part of the evolutionary diversity retained in geographically isolated strains has become increasingly relevant for the conservation of biodiversity. However, the distribution of phylogenetic diversity is still unknown to most groups, which restricts its use as a key criterion in the selection of priority areas for conservation. For this purpose it is important to obtain a phylogenetic hypothesis that includes all the known diversity of a lineage. Sampling difficulties often prevent adequate phylogeny reconstruction, and it is necessary to gather evidence to help reveal the group's history. We infer the phylogeny of Minaria, whose diversity is centered on the Espinhaço Chain, eastern Brazil, to assess the distribution of diversity and phylogenetic endemisms and to identify the areas of this Chain that harbor the highest concentration of exclusive evolutionary diversity. Four areas of high diversity and phylogenetic endemism were detected: Rio de Contas, in Bahia; Diamantina Plateau, Serra do Cipó and South of the Espinhaço Chain, in Minas Gerais. Among these, the Diamantina Plateau and the Serra do Cipó are the most relevant regions, housing 10 exclusive species and some of them are unprotected and vulnerable to human disturbances. There is a high degree of threat of extinction of M. monocoronata, the only endemic species in the south of the Espinhaço, descended from an endemic and restricted distribution, found exclusively in cangas, one of the most threatened environments of this mountain range